Gender Discrepancies in SARS-CoV-2 Pandemic Related Beliefs, Attitudes, and Practices - Pflugeisen, Bethann Mangel; Mou, Jin (Frontiers in Public Health, 2021)
Objectives: International studies suggest that males may be less likely to adhere to SARS-CoV-2 transmission mitigation efforts than females. However, there is a paucity of research in this field in the United States. The primary aim of this study was to explore the relationship of binary gender identity (female/male) with beliefs, attitudes, and pandemic-related practices in the early stages of the pandemic. Methods: This study is based on a cross-sectional, voluntary response survey. Patients who were tested for SARS-CoV-2 between March 5 and June 7, 2020 were invited to participate. All patients were tested within a large community healthcare system that serves patients through eight hospitals and hundreds of clinics across Washington State. Bivariate associations between gender and various demographics were tested using Chi-squared and Student’s t-tests. We examined associations between gender and pandemic-related beliefs, attitudes, and practices using multivariable logistic regression, accounting for potential confounding factors. Results: Females were more likely than males to agree that they (aOR=1.51, 95% CI 1.14-2.00) or their families (aOR=1.75, 95% CI 1.31-2.33) were threatened by SARS-CoV-2, or that their own behavior could impact transmission (aOR=2.17, 95% CI 1.49-3.15). Similarly, females were more likely to agree that social distancing (aOR=1.72, 95% CI 1.19-2.46), handwashing (aOR=3.27, 95% CI 2.06-5.21), and masking (aOR=1.41, 95% CI 1.02-1.94) were necessary to slow SARS-CoV-2 spread. Females were significantly less likely to visit outside of their social distancing circle (aOR=0.62, 95% CI 0.47-0.81), but among those who did, practices of social distancing (aOR=1.41, 95% CI 0.89-2.23), remaining outdoors (aOR=0.89, 95% CI 0.56-1.40), and masking (aOR=1.19, 95% CI 0.74-1.93) were comparable to males, while females practiced handwashing more than males (aOR=2.11, 95% CI 1.33-3.34). Conclusions: Our study suggests that gender disparate beliefs, attitudes, and practices existed in the early stages of the SARS-CoV-2 pandemic. Efforts should be tailored to encourage males to engage with mitigation efforts in ongoing pandemic-related public health campaigns.